2014
DOI: 10.1001/jamasurg.2014.514
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y Gastric Bypass Surgery or Lifestyle With Intensive Medical Management in Patients With Type 2 Diabetes

Abstract: IMPORTANCE Emerging data support bariatric surgery as a therapeutic strategy for management of type 2 diabetes mellitus. OBJECTIVE To test the feasibility of methods to conduct a larger multisite trial to determine the long-term effect of Roux-en-Y gastric bypass (RYGB) surgery compared with an intensive diabetes medical and weight management (Weight Achievement and Intensive Treatment [Why WAIT]) program for type 2 diabetes. DESIGN, SETTING, AND PARTICIPANTS A 1-year pragmatic randomized clinical trial wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(157 citation statements)
references
References 40 publications
8
145
0
4
Order By: Relevance
“…Two of the eleven included studies were RCTs [51,52]. Six of the studies included in this review had a strong overall quality rating, according to the EPHPP quality assessment tool used ( Table 2).…”
Section: Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the eleven included studies were RCTs [51,52]. Six of the studies included in this review had a strong overall quality rating, according to the EPHPP quality assessment tool used ( Table 2).…”
Section: Qualitymentioning
confidence: 99%
“…The most commonly cited co-morbidities were diabetes and cardiovascular disease. The individual study sample size ranged from 43 to 1276 [52,39]. The majority of participants in the studies were female and mean age ranged from 39 years [55] to 48 years [39] which is representative of the BS population in the UK [14] Group differences in baseline characteristics were noted in most of the studies apart from the four controlled trials [51,52,56,39] and Buddeberg-Fischer et al [54].…”
Section: Representativenessmentioning
confidence: 99%
See 2 more Smart Citations
“…This study compared LSG to gastric bypass (LSAGB) for the treatment of T2DM in Asian patients with BMI <35 kg/m 2 and was the first study to prove that gastric bypass (a duodenum exclusion procedure) had better efficacy on T2DM remission than LSG (non‐duodenum exclusion procedure). Following this landmark study, many RCT focusing on the comparison of metabolic surgery and medical treatment for the treatment of T2DM have been carried out and universally showed that metabolic surgery is more effective than medical treatment in glycemic control 91, 92, 93, 94, 95, 96, 97, 98, 99. Table 2 lists the results of RCT trials on surgical treatment versus medical treatment for T2DM.…”
Section: From Bariatric To Metabolic Surgerymentioning
confidence: 99%